MEASUREMENTS OF THE LINESHAPE OF THE Z(0) AND DETERMINATION OF ELECTROWEAK PARAMETERS FROM ITS HADRONIC AND LEPTONIC DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; Andreazza, A; et al. (1994)
During the LEP running periods in 1990 and 1991 DELPHI has accumulated approximately 450000 Z0 decays into hadrons and charged leptons. The increased event statistics coupled with improved analysis techniques and improved knowledge of the LEP beam energies permit significantly better measurements of the mass and width of the Z0 resonance. Model independent fits to the cross sections and leptonic forward-backward asymmetries yield the following Z0 parameters: the mass and total width Mz = 91.187 ± 0.009 GeV, ΓZ = 2.486 ± 0.012 GeV, the hadronic and leptonic partial widths Γhad = 1.725 ± 0.012 GeV, Γl, = 83.01 ± 0.52 MeV, the invisible width Γinv = 512 ± 10 MeV, the ratio of hadronic to leptonic partial widths Rl = 20.78 ± 0.15, and the Born level hadronic peak cross section σ0 = 40.90 ± 0.28 nb. Using these results and the value of αs determined from DELPHI data, the number of light neutrino species is determined to be 3.08 ± 0.05. The individual leptonic widths are found to be: Γe = 82.93 ± 0.70 MeV, Γμ = 83.20 ± 1.11 MeV and Γτ = 82.89 ± 1.31 MeV. Using the measured leptonic forward-backward asymmetries and assuming lepton universality, the squared vector and axial-vector couplings of the Z0 to charged leptons are found to be gvl2 = (1.47 ± 0.51) × 10-3 and gAl2 = 0.2483 ± 0.0016. A full Standard Model fit to the data yields a value of the top mass mt = 115-82+52(expt.)-24+23(Higgs) GeV, corresponding to a value of the weak mixing angle sin2 θefflept = 0.2339±0.0015(expt.)-0.0004+0.0001(Higgs). Values are obtained for the variables S and T, or ∈1 and ∈3 which parameterize electroweak loop effects.